Translating Cultures Unveiling the Art of Uzbek Literary Transformations - Nilufar Abdukhafizovna Khalimova (Universitas Muhammadiyah Sidoarjo, 2024)
This study conducts a linguocultural analysis of 20th-century Uzbek literary translations, illuminating the complex interaction between language and culture, particularly in the nuanced translation of stories like